Microencapsulation of basil essential oil: utilization of gum arabic/whey protein isolate/maltodextrin combinations for encapsulation efficiency and in vitro release - Ozdemir, Necla; Bayrak, Ali; Tat, Tuba; Altay, Filiz; Kiralan, Mustafa; Kurt, Abdullah (Springer Science and Business Media LLC, 2021)
Basil (Ocimum basilicum L.) essential oil (BEO) draws attention for its phenolic acid content which causes it to be used as a medicinal agent and food additive. However, its vulnerability to environmental and technological factors can be an obstacle to its implementation in industry and, at this point, encapsulation technology is utilized. The objective of this study was to encapsulate BEO using a spray drying technique to extend its shelf life, and to evaluate the influence of different wall material formulations on the properties of the BEO microcapsules. Gum Arabic (GA), maltodextrin (MD), and whey protein isolate (WPI) were used as wall materials and four different formulations were studied: GA, GA:WPI (1:1, w/w), GA:WPI:MD (1:1:1, w/w), and WPI:MD (1:1, w/w). The GA, GA:WPI, and GA:WPI:MD emulsions displayed shear thinning behavior (pseudoplastic, n < 1) while the WPI:MD emulsion behaved as a Newtonian fluid (n = 1). The GA (0.21 µm) and WPI:MD (0.25 µm) emulsions, having smaller droplets, exhibited no creaming. Powder recovery values of the BEO microcapsules ranged from 65.92% to 76.39%. The encapsulation efficiency of the microcapsules varied between 82.34% and 87.19%; the highest value was determined for the GA:WPI:MD microcapsules. Optimal thermal stability and higher Tg values were obtained for the GA:WPI and GA:WPI:MD formulations. The ternary combination also had the highest in vitro eugenol release (58.97%) in ethanol. Finally, the GA:WPI:MD formulation demonstrated a high product yield and encapsulation efficiency with better physicochemical properties for encapsulation of BEO.